A docência e organização do trabalho em uma escola multisseriada no município de Acará – PA - ANDRÉ, Maria Elieni Cardoso de (2021)
This research discusses the Teaching and Work Organization of a teacher in a multi-grade school located in the peasant space in a riverside area of Acará (PA), aiming at what practices she uses to develop the teaching work and if there is any relation with the local context, making an analysis about the education aimed at the field, since the Organization of Teaching Work is an indispensable tool to order the works to be done in the school in order to reach the intended objectives. It is an empirical and bibliographical research, which incorporated, besides theoretical references related to the theme, observations of the teacher's practices in the classroom as well as the relationship between educator and students. The research links point to a differentiated teaching practice that encompasses the subjects of that locality and the local culture, incorporating their ways of being and living in the curriculum. Considering the importance of analyzing how teaching occurs in the multi-grade class, taking into account the daily reality of students, as well as verify the methodologies used to acquire the teaching and learning of these students. It is necessary to understand that teaching in multigrade classes seeks to maintain the cultural identity and autonomy that exists between the subjects who occupy those spaces. To theoretically support our writings, we sought some authors who were introduced to us during the formation of the Degree Course in Rural Education, they are: Arroyo (1999, 2013), Benjamin (2000), Fernandes (1999), Hage (2005, 2011, 2015), Molina (2012), Silva (2006, 2009) and others.